2017
DOI: 10.3390/genes8050135
|View full text |Cite
|
Sign up to set email alerts
|

Combination of RNA Interference and Stem Cells for Treatment of Central Nervous System Diseases

Abstract: RNA interference (RNAi), including microRNAs, is an important player in the mediation of differentiation and migration of stem cells via target genes. It is used as a potential strategy for gene therapy for central nervous system (CNS) diseases. Stem cells are considered vectors of RNAi due to their capacity to deliver RNAi to other cells. In this review, we discuss the recent advances in studies of RNAi pathways in controlling neuronal differentiation and migration of stem cells. We also highlight the utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…16 In some researches, it was shown that the introduction of therapeutic drugs, transgenes, and small interfering RNAs (siRNAs) into MSCs did not interfere with their proliferation and differentiation capacities. 17 Regarding the above-mentioned examples, it can be concluded that using the nanocarriers that have been successful in drug-delivery systems, including dendrimers, for delivering genes to SCs can be helpful in extending the survival of these cells and preventing their senescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In some researches, it was shown that the introduction of therapeutic drugs, transgenes, and small interfering RNAs (siRNAs) into MSCs did not interfere with their proliferation and differentiation capacities. 17 Regarding the above-mentioned examples, it can be concluded that using the nanocarriers that have been successful in drug-delivery systems, including dendrimers, for delivering genes to SCs can be helpful in extending the survival of these cells and preventing their senescence.…”
Section: Introductionmentioning
confidence: 99%
“…SCs are generally hard‐to‐transfect and their differentiation status, viability, tumorigenicity and capacity for migration and invasion should be controlled during transfection 16 . In some researches, it was shown that the introduction of therapeutic drugs, transgenes, and small interfering RNAs (siRNAs) into MSCs did not interfere with their proliferation and differentiation capacities 17 …”
Section: Introductionmentioning
confidence: 99%